The Influence of Using Web-Based Articles and Videos towards Students’ Grammar Mastery - Sri Ariani; Ardian Nuri (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study is aimed to find out whether there is any influence of using web-based articles and videos towardss students’ grammar mastery or not. The approach of this research was quantitative. Pretest, posttest and questionnaire were used as the instruments to generate the data. The subjects of this research were the second grade students of MA Malaka, North Lombok. The results showed that there was increment of pre-test (55.50) and the post-test (77.88). The difference between the pre-test and the post-test was statistically significant (0.00 < 0.05). It indicated that web-based articles and videos increased students’ grammar achievement. The result of questionnaire showed that 67.4% of students chose ‘agree’ in the statement of students’ attitude in web-based articles and videos as the learning media. It suggested that web-based articles and videos usefull as alternative media in teaching grammar